2011
DOI: 10.1056/nejmoa1013961
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Health Outcomes in Women Exposed In Utero to Diethylstilbestrol

Abstract: In utero exposure of women to DES is associated with a high lifetime risk of a broad spectrum of adverse health outcomes. (Funded by the National Cancer Institute.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
267
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 379 publications
(282 citation statements)
references
References 33 publications
3
267
2
8
Order By: Relevance
“…L'augmentation du nombre de cancers de la thyroïde et du testicule, beaucoup moins fréquents [5], n'est pas visible ici (© Ellen Benhamou, Institut Gustave Roussy, service de biostatistiques et Hélène Sancho-Garnier). [9], la survenue d'un cancer rare du vagin à petites cellules a facilité la démonstration épidémiologique de l'agent responsable, ce n'est pas le cas des cancers du sein et de la prostate.…”
Section: Perturbateurs Endocriniens Et Incidence Des Cancers Hormonodunclassified
See 2 more Smart Citations
“…L'augmentation du nombre de cancers de la thyroïde et du testicule, beaucoup moins fréquents [5], n'est pas visible ici (© Ellen Benhamou, Institut Gustave Roussy, service de biostatistiques et Hélène Sancho-Garnier). [9], la survenue d'un cancer rare du vagin à petites cellules a facilité la démonstration épidémiologique de l'agent responsable, ce n'est pas le cas des cancers du sein et de la prostate.…”
Section: Perturbateurs Endocriniens Et Incidence Des Cancers Hormonodunclassified
“…une exposition précoce de nouveau-nés à de faibles doses de BPA facilite à l'âge adulte l'apparition de cancers in situ de la prostate susceptibles d'évoluer vers des cancers invasifs chez les rats plus âgés [9,14,15].…”
Section: Deux Caractéristiques Généralesunclassified
See 1 more Smart Citation
“…DES-exposed daughters were found to have abnormally shaped uteri, which led both to infertility problems and premature births of their offspring [17,18]. Additional follow-up of DESexposed mothers and daughters showed that each group appeared to have an increased risk of developing breast cancer [19][20][21][22].…”
mentioning
confidence: 99%
“…Most recently, National Cancer Institute (NCI) collaborative studies showed that in-utero exposure of women to DES is associated with a high lifetime risk of a broad spectrum of adverse health outcomes, including an increased risk of breast cancer in daughters 40 years of age and older [22]. For DES-exposed sons, an increased risk of cancer has not been demonstrated [23] but they do have increased prevalence of maldescent of the testes, epididymal cysts, hypotrophic testes, and varicoceles [24][25][26][27].…”
mentioning
confidence: 99%